The Interest of Undergraduate Students in Co-curricular Activities in Relation to their Leadership Skills (American Journal of Education and Technology, 2023)
The study explores the levels of interest of undergraduate students in Co-curricular Activities and their level of Leadership skills about their gender, stream of education and locality. The investigator collected data from 160 Undergraduate students from different Degree colleges of Balasore municipality having arts and science as their streams of studies through stratified random sampling technique. The researcher used the self-made Interest Inventory on Co-curricular Activities and Leadership skill Questionnaire to collect data. The students’ responses were analyzed using Frequency and Percentage Analysis, Mean, Standard deviation, t-test, and Karl Pearson’s correlation method. The study reveals that irrespective of the factors like gender, locality and streams of education, majority of the Undergraduate students have medium levels of interest in co-curricular activities and Leadership skills. Gender seems to be associated with the students’ level of interest in Co-curricular Activities and Leadership skills. Female students are better in their interest in Co-curricular Activities and Leadership skills than the Male students. Further, it is observed that level of Leadership skills of the students depends highly on the interest in Co-curricular Activities, higher level of interest in Co-curricular Activities of the undergraduate students leads to higher Leadership skills.